Gambaran Tingkat Pengetahuan Remaja Mengenai Penatalaksanaan Dismenore Secara Non-Farmakologis - Putu Luna Lakaruna Wigraha Dewi; Asdiwinata, I Nyoman; Ayu Putu Satya Laksmi, I Gusti (Pustaka Galeri Mandiri, 2026)
Dysmenorrhea can interfere with adolescent girls' physical and emotional activities, but few seek medical help, so non-pharmacological management such as warm compresses, exercise, relaxation, massage and knee chest position is highly dependent on adolescents' level of knowledge about their effectiveness and how to apply them. This study aims to find out the overview of adolescents' knowledge level regarding the management of dysmenorrhea in a non-pharmacological manner at SMP Negeri 1 Ubud. This study uses a quantitative design with Proportionate Stratified Random Sampling with a sample of 222 people. Data were collected through a questionnaire on adolescent knowledge level regarding the management of dysmenorrhea in a non-pharmacological manner which has been tested for validity with a result of 0.382 and a reliability test with a result of 0.819. The results of respondent identification found that the most respondents were in class VIII with a total of 81 respondents (36.5%), most of the respondents were 13 years old, namely 80 respondents (36.0%), the most respondents experienced menstruation for 6-7 days with 77 respondents (34.7%), the most dysmenorrhea management was carried out by rest, namely 100 respondents (45.0%), and as many as 8 respondents (3.6%) used pharmacological methods. The level of adolescent knowledge about the management of dysmenorrhea non-pharmacologically was in the sufficient category, namely 119 people (53.6%), 83 people (37.4%), and 20 people (9.0%) with poor knowledge. Education to adolescent girls about reproductive health, especially about the management of dysmenorrhea in a non-pharmacological manner, needs to be done to increase adolescent knowledge